2004
DOI: 10.1016/j.jdeveco.2003.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration economies and productivity in Indian industry

Abstract: The primary objective of this paper is to examine the extent to which agglomeration economies contribute to economic productivity. We distinguish three sources of agglomeration economies: (1) at the firm level from improved access to market centers, (2) at the industry level from intra-industry localization economies, and (3) at the regional level from inter-industry urbanization economies. There is considerable variation in the sources and magnitudes of agglomeration economies between industrial sectors-in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(157 citation statements)
references
References 33 publications
6
147
0
1
Order By: Relevance
“…Congestion may be especially severe if infrastructure is a bottleneck to economic activities. For instance, Lall, Shalizi, and Deichmann (2004) found that geographic concentration of the same industry lowers the productivity of Indian firms, whereas access to markets through improvement in inter-regional infrastructure has favorable effect. Furthermore, the fiercer competition in product and factor markets can suppress a firm's mark-up and productivity through lower product prices and higher inputs costs.…”
Section: An Overview Of Studies On Agglomerationmentioning
confidence: 99%
“…Congestion may be especially severe if infrastructure is a bottleneck to economic activities. For instance, Lall, Shalizi, and Deichmann (2004) found that geographic concentration of the same industry lowers the productivity of Indian firms, whereas access to markets through improvement in inter-regional infrastructure has favorable effect. Furthermore, the fiercer competition in product and factor markets can suppress a firm's mark-up and productivity through lower product prices and higher inputs costs.…”
Section: An Overview Of Studies On Agglomerationmentioning
confidence: 99%
“…Summary statistics such as the total road length in a state/province or straight-line distance to ports or urban agglomerations are poor proxies for the complexity inherent in a national or regional transportation network. We therefore use a digital geographic representation of Mexico's transport network to compute an index of accessibility for each municipio as a simple measure of accessibility and potential market integration (see Lall et al 2004). The index summarizes the size of the potential market that can be reached from a particular point given the density and quality of the transport network within that region.…”
Section: Location Characteristicsmentioning
confidence: 99%
“…Using terminology from Fujita et al (2000), all of these positive externalities are "centripetal forces" that will benefit the industry, and according to O'Sullivan (2003), the economy will enjoy lower costs and higher productivity. Thus, in the MSV model, F will be a decreasing function of n, and 伪 will be an increasing function of n. In addition to supply-side externality, agglomeration economies will be realized in the form of "thick-market externalities," which will reduce asymmetric information for consumers and will give them better opportunities to compare the prices and quality of goods (Lall et al 2004).…”
Section: Concentration and Congestion: Measurementmentioning
confidence: 99%
“…Lall et al (2004) suggested an alternate approach using industry employment in the district, and measured the localization economies within a sector. Data from the Indian manufacturing industry show negative coefficients for concentration economies from three industries, implying that benefits from external economies are "offset" by diseconomies from increasing wages and rents, as well as increasing transportation costs due to congestion.…”
Section: Concentration and Congestion: Measurementmentioning
confidence: 99%